Increased Rates of Mild Traumatic Brain Injury Among Older Adults in US Emergency Departments, 2009-2010. Issue 5 (September 2016) - Albrecht, Jennifer S.; Hirshon, Jon Mark; McCunn, Maureen; Bechtold, Kathleen T.; Rao, Vani; Simoni-Wastila, Linda; Smith, Gordon S.
Abstract : Objective: To estimate rates of emergency department (ED) visits for mild traumatic brain injury (TBI) among older adults. We defined possible mild TBI cases to assess underdiagnoses. Design: Cross-sectional. Setting: National sample of ED visits in 2009-2010 captured by the National Hospital Ambulatory Medical Care Survey. Participants: Aged 65 years and older. Measurements: Mild TBI defined by International Classification of Diseases, Ninth Revision, Clinical Modification, codes (800.0x-801.9x, 803.xx, 804.xx, 850.xx-854.1x, 950.1x-950.3x, 959.01) and a Glasgow Coma Scale score of 14 or more or missing, excluding those admitted to the hospital. Possible mild TBI was defined similarly among those without mild TBI and with a fall or motor vehicle collision as cause of injury. We calculated rates of mild TBI and examined factors associated with a diagnosis of mild TBI. Results: Rates of ED visits for mild TBI were 386 per 100 000 among those aged 65 to 74 years, 777 per 100 000 among those aged 75 to 84 years, and 1205 per 100 000 among those older than 84 years. Rates for women (706/100 000) were higher than for men (516/100 000). Compared with a possible mild TBI, a diagnosis of mild TBI was more likely in the West (odds ratio = 2.31; 95% confidence interval, 1.02-5.24) and less likely in the South/Midwest (odds ratio = 0.52; 95% confidence interval, 0.29-0.96) than in the Northeast. Conclusions: This study highlights an upward trend in rates of ED visits for mild TBI among older adults.